A Comparison of Hearing Assessment Between Automated and Manual Audiometry of Person Who Receive Health Check-ups at a Hospital, Thailand - Winuntamalakul, Possavee; Patipat, Pichitra; Meepradit, Parvena (Disease Control Journal, 2026)
This cross-sectional analytical study aimed to compare automated and manual audiometry across three important dimensions: hearing test outcomes, testing duration, and user satisfaction. Twenty-four participants (forty-eight ears) underwent hearing threshold testing at frequencies ranging from 500 to 8000 Hz by both automated and manual audiometry. The data were analyzed using descriptive statistics and analytic statistics. The results showed that the hearing threshold differences between the two methods did not exceed 10 decibels at any frequency. Furthermore, a statistically significant high correlation was found between automated and manual audiometry (p<0.05), confirming the reliability of the automated method. Also, automated audiometry was significantly faster than the manual approach (p<0.05). Regarding user satisfaction, overall levels were similar, although participants expressed lower satisfaction with the duration of the automated test (p<0.05). These findings suggest that automated audiometry provides results comparable to manual testing while saving time. The method therefore shows promise for integration into medical surveillance programs. Moreover, its use in hearing conservation program could further enhance accessibility to timely screenings. However, improvements in the testing procedure or user instructions are recommended to address participant concerns about test duration.